Discovery of small molecules through pharmacophore modeling, docking and molecular dynamics simulation against Plasmodium vivax Vivapain-3 (VP-3). Issue 5 (May 2018) - Saddala, Madhu Sudhana; Adi, Pradeepkiran Jangampalli
Abstract: Vivapain-3(VP-3) protein is a family of cysteine rich proteases of malaria parasite is extensively reported to participate in a range of wide cellular processes including survival. VP-3 of plasmodium recognized as an attractive drug target in vector-borne diseases like malaria. In the present study we robust a homology model of VP-3 protein and generated the pharmacophore based models adapted to screen the best drug like compounds from PubChem database. Our results finds the fourteen best lead molecules were mapped with core pharmacophore features of VP-3 and top hits were further evaluated by molecular dynamics simulation and docking studies. Based on the molecular dynamics simulation and docking results and binding vicinity of ligand molecules, top five i.e., CID 74427945, CID 74427946, CID 360883, CID193721 and CID 51416859 showed the best docking scores with good molecular interactions against VP-3. Furthermore in silico ADMET and in vitro assays clearly exhibited that out of five three CID74427946, CID74427945 and CID360883 ligand molecules showed the best promising inhibition against VP-3. The present study believed to provide significant information of potential ligand inhibitors against VP-3 to design and develop the next generation malaria therapeutics through computational approach.